Microwave plasma characteristics during bias-enhanced nucleation of diamond: An optical emission spectroscopic study - Whitfield, MD; Jackman, R; Rodway, D; Savage, J; Foord, J (1996)
A negative bias applied to a nondiamond substrate at the initiation of microwave plasma-enhanced chemical-vapor deposition of thin-film diamond can lead to diamond nucleation, high crystalline density, and an improved level of crystallographic alignment. In this work, optical emission spectroscopy has been used to study changes in the chemical species within the plasma that occur as a result the applied bias to a tungsten substrate. The ratio of C2 to CH species detected changes considerably as does the atomic hydrogen intensity as the bias is applied. Both effects appear to be greatest near the substrate surface. The results are discussed in terms of possible origins for the bias-enhanced nucleation process. © 1996 American Institute of Physics.